The Use of Rubber Manufacturing Waste as Concrete Additive - Mohammad Zaki, M. F.; Isa, N. F.; Ahmad Sofri, L.; Abdul Rahim, M.; Md Ghazaly, Z.; Bidin, N. (Journal of Advanced Research in Applied Mechanics, 2020)
The enormous quantity of vehicle nowadays, to some extent, undermined the environment. Increasing the number of cars indirectly produce high volume of waste tires. The presence of waste tires is a major factor that contributes to the risk of breeding places for mosquitoes, while burning tires will cause air pollution. To minimize this problem from becoming more serious, many alternatives have been implemented recently, such as the application of waste tire as a construction material. The main concept is to reduce air pollution and to produce concrete that is environmentally friendly and practical for the construction industry. Based on these objectives, this study was conducted to determine whether rubber tires can act as a concrete additive. Pieces of waste tire replaced the aggregate in the concrete mix design. The size of the tire rubber was in the range between 10 – 20 mm. The mixture of coarse aggregate replacement percentages of rubber tires by weight were 1%, 3 % and 5%. Concrete curing methods consist of wet and dry methods. All of the samples were preserved for 28 days. The results were then compared with the control concrete of mix rubber tires. Based on the research finding, rubber concrete mix has higher workability compared to control concrete mix. However, the compressive strength of rubber concrete mix is slightly lower than control concrete mix, but it is still acceptably strong. The analysis of the experimental results showed that replacing 2.5% of coarse aggregates by shredded tire increased the compressive strength of the concrete slightly but replacing more than 2.5% of coarse aggregates reduces the concrete strength.